2003
DOI: 10.1093/ajcn/77.5.1098
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and the lipid response to dietary intervention: a systematic review

Abstract: There is wide interindividual variation in the lipid and lipoprotein responses to dietary change, and the existence of consistent hypo- and hyperresponders supports the hypothesis that responsiveness is related to genetic variation. Many studies have investigated the possibility that the heterogeneity in responsiveness to changes in dietary fat, cholesterol, and fiber intake is explained by variation in genes whose products affect lipoprotein metabolism, eg, apolipoproteins, enzymes, and receptors. A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
2
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 86 publications
2
137
2
7
Order By: Relevance
“…Responsiveness to dietary fat manipulation is recognised to be highly variable, with genetic variability known to be partly responsible. The systematic review by Masson et al (2003) includes studies that have examined the impact of genotype on the responsiveness of fasting lipids to dietary cholesterol (fifteen individual studies) and total fat or fatty acid composition (thirty-six individual studies; mainly manipulation of SFA, MUFA and PUFA ratios). Three of the cholesterol-manipulation studies have reported a greater circulating cholesterol response in E4 carriers.…”
Section: Apoe Genotype and Responsiveness To Dietary Fat Manipulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Responsiveness to dietary fat manipulation is recognised to be highly variable, with genetic variability known to be partly responsible. The systematic review by Masson et al (2003) includes studies that have examined the impact of genotype on the responsiveness of fasting lipids to dietary cholesterol (fifteen individual studies) and total fat or fatty acid composition (thirty-six individual studies; mainly manipulation of SFA, MUFA and PUFA ratios). Three of the cholesterol-manipulation studies have reported a greater circulating cholesterol response in E4 carriers.…”
Section: Apoe Genotype and Responsiveness To Dietary Fat Manipulationmentioning
confidence: 99%
“…Three of the cholesterol-manipulation studies have reported a greater circulating cholesterol response in E4 carriers. Eleven of the studies that manipulated dietary fat have demonstrated a genotype · treatment interaction, with the E4 subgroup being generally the most responsive (Masson et al 2003). For example, in the Schaefer et al (1997) study (n 148) a National Cholesterol Education Program…”
Section: Apoe Genotype and Responsiveness To Dietary Fat Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Again, this FABP2 Ala54Thr polymorphism was shown to modify the association between dietary saturated fat intake and lipid cholesterol concentrations as well as markers of insulin resistance in the Italian population. 49 Published reviews of gene-diet interactions clearly show that dietary factors modify the predisposing or protective effect of gene loci 50 and that the effect varies between populations. 43,50 To our knowledge, gene-environment interactions have never been studied in Northern First Nations populations.…”
Section: Dietary Transition and Genetic Predispositions Of Northern Fmentioning
confidence: 99%
“…This led to the emerging concept that such variable metabolic responses might derive from interactions between the individual's genetic background and dietary factors [27,46]. In that line, the variability of response would thereby result, at least in part, from the presence of allelic variants in the genes coding for proteins involved in the intermediary metabolism such as apolipoproteins, lipid-processing enzymes, lipid transfer proteins and receptors binding lipoproteins [24,41].…”
Section: Introductionmentioning
confidence: 99%